ACCOUNTING AND ANALYTICAL PROVISION OF ENVIRONMENTAL RESPONSIBILITY FOR THE NEEDS OF COMPETITIVE ENTERPRISE MANAGEMENT - IVANCHENKOVA, Larysa; YAKOVENKO, Alla; ZHADANOVA, Yuliia; LAGODIIENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the set of methods, approaches, and standards that form the accounting and analytical system of environmental responsibility and can properly integrate environmental information into the enterprise management system based on sustainability and competitiveness. The concept and structure of the accounting system and analytical support of a socially responsible enterprise are analyzed, and the relationship with the environmental and reputational components, their current state, and development are determined. It has been clarified which tools should be used to account for and analyze the costs of ecosystem services. The main directions of enterprise management activities for transforming the accounting processes and analyzing information resources have been determined. In connection with the need to quickly respond to critical changes in a dynamic society, the achievement of a sustainable management policy requires the presence of a solid automated system of accounting and analytical support for maintaining gains and developing a modern competitive strategy through sustainable development and with the help of the ecological accounting method, proposed by Müller-Wenk (Müller-Wenk), qualification standards for sustainable development, methods of integrated of environmental accounting of the Italian ENI Foundation named after Enrico Mattei (Fondazione Eni Enrico Mattei - FEEM) - Mass and Energy Flow Cost Accounting (MEFCA). Environmental aspects of the company’s activity can predict future resource needs and the impact of activities on the environment. Also investigated as a component of the competitiveness of a sustainable enterprise is the development of a compensation mechanism for damage, losses, and the need for recovery from armed aggression. These aspects allow the management of the enterprise to strengthen the data system of strategic planning for decision-making on environmental policy, provided they are integrated into the general management system of the enterprise. The proposed accounting and analytical system of environmental responsibility is for forming a sustainable and appropriate enterprise culture, minimizing the negative environmental impact, and increasing management efficiency.